Strategi Optimalisasi Fundraising Dana Zakat di Lembaga Amil Zakat OPSEZI (tahun 2011-2015) - Ambok Pangiuk; Novi Mubyarto; Rohmat Agung Setiawan (Indonesian Journal of Islamic Economics and Business, 2018)
This paper aims to find out the strategies in fundraising, management and distribution systems and the constraints faced by the organization and the optimal level of the strategies applied. This paper uses a qualitative approach with data collection methods through observation, interviews and documentation. The following results and conclusions are first, the fundraising strategy is broadly divided into two, namely direct fundraising (directly) and indirect fundraising (indirectly). Second, the management and distribution system carried out by LAZ OPSEZI is more on the collection system and is directly distributed even though there are certain programs that are managed first. Third, the obstacles faced by this institution in collecting funds include the lack of existing human resources, less than optimal cooperation with the government and the lack of public understanding of zakat and amil zakat institutions. Fourth, based on research through data collection, the fundraising system implemented in 2015-2016 runs quite optimally, this is based on the achievement targets made, the amount of achievement in that year and compared from the previous year